Technology Within and Across Firms - Cirera, Xavier; Comin, Diego; Cruz, Marcio; Lee, Kyung Min (World Bank, Washington, DC, 2020)
This study collects data on the sophistication of technologies used at the business function level for a representative sample of firms in Vietnam, Senegal, and the Brazilian state of Ceara. The analysis finds a large variance in technology sophistication across the business functions of a firm. The within-firm variance in technology sophistication is greater than the variance in sophistication across firms, which in turn is greater than the variance in sophistication across regions or countries. The paper documents a stable cross-firm relationship between technology at the business function and firm levels, which it calls the technology curve. Significant heterogeneity is uncovered in the slopes of the technology curves across business functions, a finding that is consistent with non-homotheticities in firm-level technology aggregators. Firm productivity is positively associated with the within-firm variance and the average level of technology sophistication. Development accounting exercises show that cross-firm variation in technology accounts for one-third of cross-firm differences in productivity and one-fifth of the agricultural versus non-agricultural gap in cross-country differences in firm productivity.